ANALISIS STRUKTURAL PADA ANTOLOGI PUISI HUJAN BULAN JUNI KARYA SAPARDI DJOKO DAMONO - Heryanti, Sintia Putri; Agustiani, Tanti (Jurnal Bahastra, 2024)
This study uses an anthology of poetry by Sapardi Djoko Damono entitled Rain in June. This study will use the poetry anthology Rain in June as the object of research. The poetry anthology Rain in the Month of June consists of 102 titles of poems written between 1959-1994. Meanwhile, the poems that will be used as research objects only consist of three poems with the titles "June Rain", "I Want" and "In My Prayers". The selection of the three poems is based on the theme that is considered the same by the researcher, namely the theme of love. The researcher will use a qualitative research method, the method used in this qualitative research is a descriptive analysis method, that is, the research is not only limited to collecting data, but the research also analyzes and interprets the data. The focus of research in this case is how the inner and physical elements of the poem Rain in June by Saprdi Djoko Damono. The data collection techniques carried out by researchers are reading and understanding poetry. The researcher read and understood the poems "Rain in the Month of June", "I Want" and "In My Prayers" by Sapardi Djoko Damono, then understood the structure and transformation of the poems. Data analysis techniques in research use three main components: Data reduction is a selection process, focusing attention on simplification, abstraction and transformation of raw data that emerges from records in the research object of presenting data. The results and discussion found that the poems "June Rain, "I Want" and "In My Prayers" in the June Rain poetry anthology have physical elements which include theme, taste, tone and message. The inner elements contained in the poems "June Rain", "I Want" and "In My Prayers" in the June Rain poetry anthology include: diction, imagery, typography, concrete words, style, and rhyme. This study uses an anthology of poetry by Sapardi Djoko Damono entitled Rain in June. This study will use the poetry anthology Rain in June as the object of research. The poetry anthology Rain in the Month of June consists of 102 titles of poems written between 1959-1994. Meanwhile, the poems that will be used as research objects only consist of three poems with the titles "June Rain", "I Want" and "In My Prayers". The selection of the three poems is based on the theme that is considered the same by the researcher, namely the theme of love. The researcher will use a qualitative research method, the method used in this qualitative research is a descriptive analysis method, that is, the research is not only limited to collecting data, but the research also analyzes and interprets the data. The focus of research in this case is how the inner and physical elements of the poem Rain in June by Saprdi Djoko Damono. The data collection techniques carried out by researchers are reading and understanding poetry. The researcher read and understood the poems "Rain in the Month of June", "I Want" and "In My Prayers" by Sapardi Djoko Damono, then understood the structure and transformation of the poems. Data analysis techniques in research use three main components: Data reduction is a selection process, focusing attention on simplification, abstraction and transformation of raw data that emerges from records in the research object of presenting data. The results and discussion found that the poems "June Rain, "I Want" and "In My Prayers" in the June Rain poetry anthology have physical elements which include theme, taste, tone and message. The inner elements contained in the poems "June Rain", "I Want" and "In My Prayers" in the June Rain poetry anthology include: diction, imagery, typography, concrete words, style, and rhyme.